Studi Optimasi Pola Operasi Waduk Sutami Akibat Perubahan Iklim - Irvani, Harvy; Bisri, Mohammad (Fakultas Teknik, Universitas Brawijaya, 2013)
The change of global climate influences the temperature, relative humidity, sunlight time, wind rate, rain rate, and river debit. The higher intensity of rain rate after the change of climate influences the fluctuation of river debit in rainy or dry season. Flood and dryness are natural occasions, which are usually occurring. Sutami Reservoir is functioned to retain water excess from rain and river debit from Brantas River, which in the future it would be stored. River debit is used to fulfill water need in dry season. Therefore, to face the extreme effect, there is needed management planning of reservoir operation managed well and optimally. Methodology used in climate change analysis toward operation model of Sutami Reservoir is Stochastic Dynamic Program and it is obtained a policy system of operation model output before and after climate change. Based on the result of analysis, it shows that there is climate change in Sutami Reservoir where it is signed that optimally reservoir output is changed. In the table of optimally reservoir output shows that before climate change the output policy is still in good condition while after it, the output policy is change where there is any displacement of wet season and dry season in which it causes the debit to Sutami Reservoir changed from what had been expected.Key words: climate change, reservoir operation model, stochastic dynamic program